2020
DOI: 10.2166/wcc.2020.171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of meteorological indices for drought monitoring and evaluating: a case study from Euphrates basin, Turkey

Abstract: Drought incidents occur due to the fact that precipitation values are below average for many years. Drought causes serious effects in many sectors, such as agriculture, economy, health, and energy. Therefore, the determination of drought and water scarcity, monitoring, management, and planning of drought and taking early measures are important issues. In order to solve these issues, the advantages and disadvantages of five different meteorological drought indices were compared, and the most effective drought i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…SPEI was then used to justify or validate the research results. The SPEI is designed to consider precipitation (PRCP) and potential evapotranspiration (PET) in determining drought (Katipoglu et al, 2020). The SPEI accomplishes the requirements of a drought index as its multi-scalar character enables it to be used by different scientific disciplines to detect, monitor, and analyze droughts (Miah et al, 2017 andAbdullah, 2014).…”
Section: Meteorological Data Processingmentioning
confidence: 99%
“…SPEI was then used to justify or validate the research results. The SPEI is designed to consider precipitation (PRCP) and potential evapotranspiration (PET) in determining drought (Katipoglu et al, 2020). The SPEI accomplishes the requirements of a drought index as its multi-scalar character enables it to be used by different scientific disciplines to detect, monitor, and analyze droughts (Miah et al, 2017 andAbdullah, 2014).…”
Section: Meteorological Data Processingmentioning
confidence: 99%
“…Several studies have been made worldwide with these indices for different reasons so as to understand its advantages and disadvantages on different applications like drought monitoring, impacts on agriculture, the prediction of forest fires, among other objectives [5]. Consequently, some studies have been conducted to compare the usage of drought indices, like, for example, Sousa et al [17], Zargar et al [25], Paulo et al [12], Vicente-Serrano et al [8], Naumann et al [26], Silva [27], Cota et al [28], Pathak et al [29], Yang et al [21], Wang et al [13], Adnan et al [30], Bayissa et al [31], Fırat et al [32], Li et al [33], Lu et al [6], Wang et al [20], Katipoglu et al [34], among others. Vicente-Serrano et al [8] found that the SPI and SPEI have a superior capability to assess drought impacts compared to Palmer indices for monitoring drought impacts on hydrological, agricultural, and ecological areas.…”
Section: Introductionmentioning
confidence: 99%
“…In Adnan et al [30], the authors found for Pakistan that the SPI and SPEI are more suitable than scPDSI to monitor droughts. Li et al [33] and Katipoglu et al [34] concluded that SPEI is a more complete index than SPI, mostly because it takes into account evapotranspiration. Lu et al [6] discovered that the scPDSI and SPEI have a better response than the SPI, SPEI being the best between the three at identifying drought events.…”
Section: Introductionmentioning
confidence: 99%
“…Different economic sectors could lead to insufficient water resources in cities (Balana et al 2020). Since drought is a critical factor in water resources management and planning (Katipoglu et al 2020), understanding the characteristics of drought-related problems is an essential step in creating mitigation measures (Bravo et al 2021). Unlike many natural disasters that occur abruptly, drought has a slow pace and is referred to as a creeping phenomenon (Drysdale et al 2020).…”
Section: Introductionmentioning
confidence: 99%